PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE DAN KONDISI KEUANGAN PERUSAHAAN TERHADAP PEMBERIAN OPINI AUDIT GOING CONCERN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING - Sherly Sherly (Jurnal Magister Akuntansi Trisakti, 2015)
The purpose of the research is to analyze the influence mechanism of good corporate governance and company financial condition toward going concern audit opinion by using firm size as a moderating variable. The statistical method is used to examine the hypotheses on this research is logistic regression. This research uses all of the property and real estate companies that listed in the Indonesia Stock Exchange. The population in this research is 129 companies for 2011-2013 period. The result of regression shows that the mechanisms of good corporate governance ( Independent board, managerial ownership, and blockholder ownership) and company financial condition don’t have significant influence against going concern audit opinion. Interaction between mechanisms of good corporate governance (Independent board, managerial ownership, and blockholder ownership) and firm size don’t have a significant influence against going concern audit opinion. Interaction between company financial condition and firm size don’t have a significant influence against going concern audit opinion.